EDUCATION'S ROLE IN PRIMARY HEALTHCARE UTILIZATION AMONG OLDER PEOPLE IN INDONESIA - Laksono, Agung Dwi; Wulandari, Ratna Dwi; Zuardin, Zuardin; Rohmah, Nikmatur (Universitas Airlangga, 2024)
Introduction: The current situation shows that life expectancy is increasing, so the population of older people is also growing. As a vulnerable group, more senior people desperately need primary health care, and barriers to accessing services will increase vulnerability. Aim: The study aimed to investigate the impact of education on primary healthcare utilization among older people. Methods: This cross-sectional study examined 52,893 older people. It employed primary healthcare utilization as an outcome variable and education level as an exposure variable. Furthermore, the study used eight control variables: residence type, age group, gender, marital status, wealth, time travel to primary healthcare, and health insurance. We employed binary logistic regression to examine the data. Results: The study showed that older adults with primary education were 1.050 times more likely than those without to utilize primary healthcare (95% CI 1.046-1.054). Older people with secondary education were 0.643 times less likely to use primary healthcare than those without (95% CI 0.638-0.649). Older adults with secondary education were 0.378 times less likely than those without to use primary healthcare (95% CI 0.372-0.383). Furthermore, the study indicated that all control variables were significantly related to direct healthcare utilization. Conclusion: The study concluded that education level influences primary healthcare utilization among older people in Indonesia. Keywords: elderly people, education, primary healthcare, healthcare evaluation, healthcare access, public health